2015
DOI: 10.1016/j.surg.2015.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of the use of prophylactic mesh augmentation compared with primary fascial suture repair in patients at high risk for incisional hernia

Abstract: Cost-utility analysis of PSC compared to PMA for abdominal laparotomy closure demonstrates PMA to be more effective, less costly, and overall more cost-effective than PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…Our group has recently assessed the cost-utility of prophylactic mesh augmentation compared to primary fascial closure in high-risk laparotomy patients using similar techniques. 52 This analysis demonstrated a 15 percent risk reduction with prophylactic mesh augmentation, and that prophylactic mesh augmentation was more effective and less costly and thus the dominant strategy across a wide range of willingness-to-pay thresholds. As hernia techniques evolve and the challenges and often disappointing results realized following complex repairs are assessed, the future role of prophylactic mesh augmentation may become great to prevent hernia formation.…”
Section: Discussionmentioning
confidence: 80%
“…Our group has recently assessed the cost-utility of prophylactic mesh augmentation compared to primary fascial closure in high-risk laparotomy patients using similar techniques. 52 This analysis demonstrated a 15 percent risk reduction with prophylactic mesh augmentation, and that prophylactic mesh augmentation was more effective and less costly and thus the dominant strategy across a wide range of willingness-to-pay thresholds. As hernia techniques evolve and the challenges and often disappointing results realized following complex repairs are assessed, the future role of prophylactic mesh augmentation may become great to prevent hernia formation.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study performed a comparison of synthetic mesh versus acellular dermal matrix in cleancontaminated ventral hernia repair through a decision model with a lifetime perspective. 33 Synthetic mesh reinforcement had an expected cost of $15,776 (21.03 quality-adjusted life-years), while biological mesh had an expected cost of $23,844 (20.94 quality-adjusted life-years). Sensitivity analysis demonstrated that synthetic mesh was the preferred and most cost-effective strategy in 94% of simulations, supporting its overall greater cost utility.…”
Section: Costmentioning
confidence: 99%
“…one year in perfect health, often set to approximately V 50,000-100,000. 9,[31][32][33] In sensitivity analysis for the ICER calculation, the discount rate and BDI frequency were varied.…”
Section: Cost Analysismentioning
confidence: 99%